Exercise and tissue fibrosis: recent advances in therapeutic potential and molecular mechanisms - Zhao, Zheng; Zhu, Yongjia; Wan, Dongfeng (Frontiers in Endocrinology, 2025)
Tissue fibrosis represents an aberrant repair process, occurring because of prolonged injury, sustained inflammatory response, or metabolic disorders. It is characterized by an excessive accumulation of extracellular matrix (ECM), resulting in tissue hardening, structural remodeling, and loss of function. This pathological phenomenon is a common feature in the end stage of numerous chronic diseases. Despite the advent of novel therapeutic modalities, including antifibrotic agents, these have only modest efficacy in reversing established fibrosis and are associated with adverse effects. In recent years, a growing body of research has demonstrated that exercise has significant benefits and potential in the treatment of tissue fibrosis. The anti-fibrotic effects of exercise are mediated by multiple mechanisms, including direct inhibition of fibroblast activation, reduction in the expression of pro-fibrotic factors such as transforming growth factor-β (TGF-β) and slowing of collagen deposition. Furthermore, exercise has been demonstrated to assist in maintaining the dynamic equilibrium of tissue repair, thereby indirectly reducing tissue damage and fibrosis. It can also help maintain the dynamic balance of tissue repair by improving metabolic disorders, exerting anti-inflammatory and antioxidant effects, regulating cellular autophagy, restoring mitochondrial function, activating stem cell activity, and reducing cell apoptosis, thereby indirectly alleviating tissue. This paper presents a review of the therapeutic potential of exercise and its underlying mechanisms for the treatment of a range of tissue fibrosis, including cardiac, pulmonary, renal, hepatic, and skeletal muscle. It offers a valuable reference point for non-pharmacological intervention strategies for the comprehensive treatment of fibrotic diseases.